The performance of two-stage submerged anaerobic membrane bioreactor (2-sAnMBR) coupling with forward osmosis membrane (FO) for palm oil mill effluent (POME) - Wiparat Chaipetch (Prince of Songkla University, 2023)
Doctor of Philosophy (Environmental Engineering), 2023